2021
DOI: 10.1038/s41598-021-81764-w
|View full text |Cite
|
Sign up to set email alerts
|

Variability in plant trace element uptake across different crops, soil contamination levels and soil properties in the Xinjiang Uygur Autonomous Region of northwest China

Abstract: This study investigated contamination status of eight trace elements (As, Cd, Cr, Hg, Pb, Cu, Zn and Ni) in farmland soils and crops at 535 sites across the Xinjiang Uygur Autonomous Region, Northwest China. Land use types of the sampling sites included vegetable patch, grain field and orchard. Our experimental results indicated all farmland soils were considered as trace element contamination based on the Nemerow comprehensive pollution index (NCPI > 1). However, 91.97% of the crop samples were uncontamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
(154 reference statements)
0
12
0
Order By: Relevance
“…Xinjiang is one of the most important agricultural production areas in the arid and semiarid regions of China (Wang et al, 2012), but 31.1% of the existing arable land in Xinjiang has suffered soil salinization (Liang et al, 2021;. The Statistical Yearbook of Xinjiang (2015) has shown that the annual yields of these three crops (grain, vegetables, and fruits) are approximately 1.50 × 10 7 , 1.93 × 10 7 , and 0.96 × 10 7 tons, respectively (Liu W. G. et al, 2021). At present, many studies on screening indigenous PGPR have also been carried out in these crops.…”
Section: Introductionmentioning
confidence: 99%
“…Xinjiang is one of the most important agricultural production areas in the arid and semiarid regions of China (Wang et al, 2012), but 31.1% of the existing arable land in Xinjiang has suffered soil salinization (Liang et al, 2021;. The Statistical Yearbook of Xinjiang (2015) has shown that the annual yields of these three crops (grain, vegetables, and fruits) are approximately 1.50 × 10 7 , 1.93 × 10 7 , and 0.96 × 10 7 tons, respectively (Liu W. G. et al, 2021). At present, many studies on screening indigenous PGPR have also been carried out in these crops.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc has negative or poor correlations with every metal at A. o cinalis (except Co and Mn) whereas, at X. mekongensis, it has strong positive correlations with most metals. This indicates the complex correlation nature of the elements in different species of medicinal plants [49]. From Table S3, S4 and S5, it is also observed that for A. ilicifolius and A. o cinalis, As has a negative or poor correlation with the majority of the elements which may show the different sources of this metal in Sundarban mangrove soils and also in plants.…”
Section: Discussionmentioning
confidence: 80%
“…The greater hurdle in the long run will come from pH changes affecting, in turn, the survivability of buried plant seeds. In addition, contaminating elements could enter the food chain, through herbaceous plants in growing seasons and potentially place human and other consumers' health at risk 33 . Therefore, to study more precisely the effects of pollution caused by the gas refinery on the food chain, it is recommended that herbaceous plants are grown in these forest ecosystems be studied further.…”
Section: Discussionmentioning
confidence: 99%